Emerging Trends in the Social and Behavioral Sciences 2015
DOI: 10.1002/9781118900772.etrds0209
|View full text |Cite
|
Sign up to set email alerts
|

Making Sense of Control: Change and Consequences

Abstract: The concept of control in the social and behavioral sciences derives mainly from theories of motivation. Early work on control was largely descriptive, with an emphasis on individual differences in perceived control. This essay first reviews the foundational research on the development of control beliefs and their relationship to achievement and health outcomes. Next, the article summarizes more recent cutting‐edge research, which has examined trajectories of longitudinal change and the processes and mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 36 publications
1
18
0
3
Order By: Relevance
“…There have been great strides to explore how perceived control changes across the lifespan, and recently there has also been interest in exploring these variations on a more short-term basis [3]. In fact, regardless of average level of perceived control, the stability of one’s level of perceived control predicts longevity and cognitive performance [50,51].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been great strides to explore how perceived control changes across the lifespan, and recently there has also been interest in exploring these variations on a more short-term basis [3]. In fact, regardless of average level of perceived control, the stability of one’s level of perceived control predicts longevity and cognitive performance [50,51].…”
Section: Introductionmentioning
confidence: 99%
“…For example, those who perceive greater control over their health may be more likely to ignore actual health problems or not regularly go to the doctor [3]. This paradox is especially true when one perceives their health as controllable but devalues the importance of it.…”
Section: Introductionmentioning
confidence: 99%
“…Given that physical activity declines with age (Centers for Disease Control and Prevention [CDC], 2013), it is important to explore its antecedents and consequences. Although perceived control (Lachman, Agrigoroaei, & Rickenbach, 2015) and cognitive health (Salthouse, 2009) also decline on average in later life, there are individual differences and there is evidence these factors can be modified. The goal of this study is to further explore the relationship between sense of control, physical activity, and cognition throughout adulthood.…”
mentioning
confidence: 99%
“…Research on the sense of control has found that individuals with disadvantaged socioeconomic status, such as individuals with lower levels of education, unemployed individuals, or those with low-status jobs with little autonomy, and identifying with lower classes, are more likely to experience the situations in which effortful action does not affect outcomes (Kraus et al 2009; Lewis et al 1999; Ross and Mirowsky 2013). Thus, a more fundamental way of reducing inequalities in sense of control and grit as beneficial psychological resources would be to turn our attention and social investment to offering more opportunities in the form of resources, more autonomy in the workplace, and increased social support to individuals from disadvantaged backgrounds to increase their sense of control (Lachman, Agrigoroaei, and Rickenbach 2015). Grit can be developed, maintained, strengthened, or reduced throughout the life course as individuals face different challenges and opportunities and develop subjective perceptions about their agency by navigating the stratified opportunity structure.…”
Section: Discussionmentioning
confidence: 99%